Native And Borrowed Layers Of Agricultural Terminology: A LexicalSemantic Analysis - Ashurova Feruza Akhmatovna (Genius Journals, 2025)
This article provides a lexical-semantic analysis of native and borrowed terms encountered in agricultural terminology. Alongside words historically rooted in the Uzbek language and formed through the creative thinking of the people, a significant number of terms have been borrowed from other languages, particularly Russian, English, Arabic, and French. The article examines the composition, meanings, term formation, and practical importance of these terms. Furthermore, it addresses the development of the agricultural lexicon and terminology, and the necessity of balancing national linguistic features with international scientific practice
Keywords: Terminology; native layer; borrowed layer